2015
DOI: 10.1088/0953-8984/27/49/495501
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the locality of periodic subsystem density-functional theory: efficient sampling of the Brillouin zone

Abstract: In order to approximately satisfy the Bloch theorem, simulations of complex materials involving periodic systems are made n(k) times more complex by the need to sample the first Brillouin zone at n(k) points. By combining ideas from Kohn-Sham density-functional theory (DFT) and orbital-free DFT, for which no sampling is needed due to the absence of waves, subsystem DFT offers an interesting middle ground capable of sizable theoretical speedups against Kohn-Sham DFT. By splitting the supersystem into interactin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…However, small deviations are expected due to the numerics involved. An additional effect may play a role, that is, the subsystem‐specific interlocking simulation cells that eQE uses exclusively to expand the wave functions and represent the Hamiltonian (all physical potentials are represented on the physical large grid, see References 22 and 23 for details). These cells are smaller than the physical cell, and as the molecule‐surface distance is increased, the cells may cease to overlap.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, small deviations are expected due to the numerics involved. An additional effect may play a role, that is, the subsystem‐specific interlocking simulation cells that eQE uses exclusively to expand the wave functions and represent the Hamiltonian (all physical potentials are represented on the physical large grid, see References 22 and 23 for details). These cells are smaller than the physical cell, and as the molecule‐surface distance is increased, the cells may cease to overlap.…”
Section: Resultsmentioning
confidence: 99%
“…Among the available sDFT software, [ 19–21 ] the embedded Quantum ESPRESSO (eQE) software, [ 22 ] developed by us, implements sDFT and the coupled equations as shown in Equation ). It achieves almost perfect parallel scaling and has provided a quantitative model at a much reduced computational cost compared to KS‐DFT of the supersystem both for ground‐state dynamics simulations [ 23–26 ] and simulations of excited‐state dynamics. [ 27–30 ] To access excited states, we make use of the real‐time subsystem time‐dependent DFT (TDDFT) implementation in eQE, [ 28,29 ] which solves the time‐dependent Schrödinger equation within the adiabatic approximation, []22+vKSI()boldr,t+vembI()boldr,tϕiI()boldr,t=iϕiI()boldr,tt. …”
Section: Introductionmentioning
confidence: 99%
“…That is, molecular systems can be treated as nonperiodic embedded systems . In a recent work, we showed that it is possible to assign a set of k ‐points to each subsystem to sample the corresponding FBZ, and this number can be chosen according to the nature of the electronic structure of the subsystem. This finding allows us to represent each subsystem band with the smallest number of k ‐points needed to reach a target accuracy.…”
Section: Details Of the Eqe Implementationmentioning
confidence: 99%
“…We note in passing here that the theoretical and algorithmic developments in the FDE and linear‐scaling DFT communities can be quite complementary, a fact exemplified by the recent work of Andermatt et al, in which the combination of linear‐scaling DFT with FDE enabled a first‐principles‐based geometry optimization of the satellite tobacco mosaic virus in solution (a system which contains 10 000s of atoms). Quite simply put, this calculation would have remained intractable for the foreseeable future without the efficient utilization of the advances in both of these approaches.…”
Section: Introductionmentioning
confidence: 97%
“…In the first release of eQE [26], we successfully implemented semilocal (GGA) level nonadditive functionals for both NAXC and NAKE with the following main features: (1) a scheme of parallel execution to distribute the workload across subsystems resulting in low data communication achieving high parallel efficiency, (2) ab initio molecular dynamics (AIMD), and (3) applicability to periodic systems. Many large systems currently outside KS-DFT's realm of applicability have been successfully studied by eQE [30,31,32,33,34,35,36]. eQE 2.0 is capable of deploying nonlocal and meta-GGA (mGGA) XC and NAKE functionals yielding highly accurate simulations of weakly interacting subsystems.…”
Section: Introductionmentioning
confidence: 99%